In Vitro Phosphate Binding Capacity of a Dietary Supplement for Dogs and Cats - Bruni, Natascia; Martello, Elisa; Adami, Raffaella; Meineri, Giorgia; Perondi, Francesca; Costale, Annalisa; Rosso, Elena; Lippi, Ilaria (Journal of Pharmacy and Nutrition Sciences, 2022)
Hyperphosphatemia has been recognized as a serious and frequent complication in dogs and cats with Chronic Kidney Disease (CKD). The veterinary approach is mainly based on reducing phosphorus in the diet and with phosphate (P) binders. In this in vitro study we compared seven supplements with a different combination of ingredients for dogs and cats at pH 3 and 7 to estimate the P binding capacity overtime. Our results confirmed the best binding capacity of supplements at acid compared to basic condition. The P binding capacity of two products containing mainly calcium carbonate, calcium lactate-gluconate and chitosan was higher compared to the other tested at the same conditions.